Ridge preservation at implants installed immediately after molar extraction. An experimental study in the dog - Favero, Giacomo; Lang, Niklaus P.; De Santis, Enzo; Gonzalez, Brismayda Garcia; Schweikert, Michael T.; Botticelli, Daniele [UNESP] (Wiley, 2013)
Aim: To evaluate the influence of deproteinized bovine bone mineral (DBBM), in conjunction with a collagen membrane, on bone resorption at implants installed in a lingual position immediately into extraction sockets with horizontal residual buccal defects >2.0 mm. Material & methods: The pulp tissue of the mesial roots of 1M1 was removed in six Labrador dogs, and the root canals were filled with gutta-percha and cement. Flaps were elevated. The molars were hemi-sectioned and the distal roots removed. Implants were installed in a lingual position and with the shoulder flush with the buccal bony crest. After installation, defects of about 2.5 and 2.7 mm in width resulted at the buccal aspects of the test and control sites, respectively. Only in the left site (test), deproteinized bovine bone mineral (DBBM) particles were placed into the defect concomitantly with the placement of a collagen membrane. On the control sites, no biomaterials were applied. A non-submerged healing was allowed. Results: After 3 months of healing, one control implant was not integrated and was excluded from the analysis, together with the contralateral test implant. All remaining implants were integrated into mature bone. The buccal alveolar bony crest was resorbed more at the test compared with the control sites, 2.2 ± 0.9 mm and 1.5 ± 1.3 mm, respectively. The vertical resorption of the lingual plate was 1.6 ± 1.5 mm and 1.5 ± 1.1 mm at the test and control sites, respectively. Only small residual DBBM particles were found at the test sites (1.4%). Conclusion: The use of DBBM particles to fill buccal defects of ≥2.5 mm at implants installed immediately into alveolar extraction sockets did not preserve the buccal bony wall. © 2012 John Wiley & Sons A/S.
Keywords: Animal study; Bone healing; Collagen membrane; Deproteinized bovine bone mineral; Extraction socket; Immediate implants; Implant dentistry; Molars; Osseointegration; Regeneration; Ridge preservation; Type I installation